The effect of Echinococcus granulosus on spleen cells and TGF‐β expression in the peripheral blood of BALB/c mice. (March 2017) - Yin, S.; Chen, X.; Zhang, J.; Xu, F.; Fang, H.; Hou, J.; Zhang, X.; Wu, X.; Chen, X.
Summary: Cystic echinococcosis (CE) caused by the cestode Echinococcus granulosus ( E. granulosus ) is a zoonotic parasitic disease. The effective immune evasion mechanisms of E. granulosus allow it to parasitize its hosts. However, the status of the innate and adaptive immune cells and their contributions to E. granulosus progression remain poorly understood. In this study, we aimed to determine the impact of E. granulosus infection on T cells, NK cell responses and TGF‐β expression during the early infection phase in BALB/c mice. In E. granulosus infections, there was an increasing tendency in the percentage of CD4 + CD25 + T cells and CD4 + Foxp3 + T cells and peripheral blood TGF‐β levels and relative expression of the Foxp3 gene. Moreover, there were a decreasing tendency in the percentage of NK cells and NK cell cytotoxicity and the expression of NKG2D on NK cells. The TGF‐β1/Smad pathway was activated by E. granulosus in mice. Above results can be reversed by the inhibitor SB‐525334 (potent activin receptor‐like kinase 5 inhibitor). These results suggest that the TGF‐β/Smad pathway plays an important role in changes of T‐cell or NK cell responses. These results may contribute to revealing the preliminary molecular mechanisms in establishing hydatid infection.